Comparative analysis of the impact of e-cigarette vapor and cigarette smoke on human gingival fibroblasts. (December 2020) - Vermehren, M.F.; Wiesmann, N.; Deschner, J.; Brieger, J.; Al-Nawas, B.; Kämmerer, P.W.
Abstract: Human gingival fibroblasts (HGF) play a vital role in wound healing, oral cancer, and are among the first cells being exposed to e-cigarette vapor (eCV) or cigarette smoke (CS) during inhalation. Although the cell-damaging effect of CS has been well studied, the effects of eCV on gingival cells are still unclear. The aim of this in vitro study was to compare the effects of eCV and CS on HGF in terms of proliferation, metabolic activity, cell death, and formation of reactive oxygen species (ROS). After 24 h cell numbers in CS-exposed cells in contrast to eCV-exposed cells were significantly decreased compared to the control. At later points in time, such differences could no longer be observed. Compared to the control, HGF stimulated with eCV showed a significantly higher metabolic activity 1 h, 24 h, and 48 h after exposure. 24 h after exposure, the metabolic activity was increased in both test groups. No caspase 3/7 activation nor significant differences in the amount of apoptosis/necrosis among the groups were seen. Only in CS-exposed cells ROS formation was increased at 1 h, 3 h, and 6 h after exposition. In conclusion, when compared to conventional CS, a less harmful effect of eCV on HGF can be assumed. Graphical abstract: Unlabelled Image Highlights: E-cigarette vapor stimulates the metabolic activity of gingival fibroblasts. Cigarette smoke leads to the demise of fibroblasts within 24 h after exposure. Formation of ROS is increased upon exposure to cigarette smoke, but not upon exposure to e-cigarette vapor.